THÀNH PHẦN KHU HỆ CHÓ NHÀ TẠI TỈNH HÀ GIANG, VIỆT NAM - Bùi, Xuân Phương; Trịnh, Quốc Khánh; Đinh, Thế Dũng; Trần, Hữu Côi; Nguyễn, Tiến Tùng (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
DOMESTIC DOG FAUNA IN HA GIANG PROVINCE VIETNAM The domestic dog fauna in Hagiang province of Vietnam was investigated. It is found that Ha giang domestic dogs are in high proportion and consist of 8 types, among which the H’mong dogs with shortail as a Vietnamese national breed were discovered. The Vietnamese domestic dogs are distributed mainly in high moutains while the group of hybrid and exotic domestic dogs are found mainly in low moutains. The result of the observation shows that the ratio of the male domestic dogs in the young stage is high, but in the adult stage it is low. The breeding method of domestic dogs in Ha giang province is mainly natural, so it is difficult to control the breeding process and veterinary work.